Analysis of Standardized Precipitation Index with Remote Sensing Derived Drought Indices : A Case Study of South Lam Ham Pong Sub Watershed - Natnaphat Subtaweepollert; Sarawut Ninsawat; Tripathi, Nitin Kumar; Shrestha, Sangam; Thailand (HM King) (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
Drought is a natural hazard that is complicated occurrence and difficult to prevent. The present study has a main objective to identify the appropriate remotely sensed drought index to assess the drought severity in non-station based areas. Thus, the Temperature Vegetation Index (TVX), Vegetation Health Index (VHI) and Modified Perpendicular Drought Index (MPDI) are used to calculate the dryness levels of South Lam Nam Pong sub-watershed. These dryness values are compared with the Standardized Precipitation Index (SPI) values to classify the drought categories. The TVX, VHI and MPDI values are classified as a moderately drought when it is more than 50.572, less than 55.746 and less than 1.178, respectively. In addition, the time lag concept is considered to investigate the drought evolution by comparing the SPI one month time scale values with TVX, VHI and MPDI values. The results indicate that a trend line of TVX, VHI, MPDI have a best fit with a trend line of SPI one month time scale at five and seven month time lag. In conclusion, TVX is the best index to assess drought event in forest areas because it can be operated in a shorter time period than VHI and MPDI, and it show the highest correlation when compare with SPI values.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Remote Sensing and Geographic Information Systems
Thesis (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Drought forecasting -- Remote sensing; Remote sensing; Geographic information systems